Rendimiento en el aserrado para grados de calidad de las clases superiores en apariencia y remanufactura en taxones de pinos en el NE de Argentina - Winck, Rosa Ángela (2023)
The quality of the sawn wood destined for moldings and remanufacturing, especially of the higher-value upper classes, play a fundamental role when its main destination is the foreign market. The objective of this work was to evaluate the yield of sawn timber classified according to the Select and Factory standards and the percentage yield in higher quality grades. A total of 42 trees of 7 taxa from one trial were sampled. The yield (%) of higher quality tables according to both typing rules was similar between strata and taxa. However, with a trend of higher wood production in higher quality grades for the dominant stratum and the PCH, F1 × PCH and F1 taxa. This trend could be increased by resorting to these hybrid materials.